1991
DOI: 10.1104/pp.96.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Root Restriction as a Factor in Photosynthetic Acclimation of Cotton Seedlings Grown in Elevated Carbon Dioxide

Abstract: Interactive effects of root restriction and atmospheric CO2 enrichment on plant growth, photosynthetic capacity, and carbohydrate partitioning were studied in cotton seedlings (Gossypium hirsutum L.) grown for 28 days in three atmospheric CO2 partial pressures (270, 350, and Elevated atmospheric CO2 affects plant growth primarily by increasing net photosynthetic rates through an increase in CO2 partial pressure at the site of fixation in the chloroplast (26). Responses of plants to long-term exposure of elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
230
9
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(250 citation statements)
references
References 28 publications
(47 reference statements)
7
230
9
4
Order By: Relevance
“…Our results clearly show that an initial growth stimulation can eventually be annulled by physiological or morphological adaptations. Cure & Acock (1986) argued that a strong sink strength is required for maintaining high photosynthetic activity at elevated CO2 and Thomas & Strain (1991) showed that a reduced photosynthetic capacity can be associated with a small rooting volume. Arp (1991) analyzed 14 observations and showed that a small rooting volume (pot size < 3-5 1) was probably responsible for photosynthetic acclimation under high CO^.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly show that an initial growth stimulation can eventually be annulled by physiological or morphological adaptations. Cure & Acock (1986) argued that a strong sink strength is required for maintaining high photosynthetic activity at elevated CO2 and Thomas & Strain (1991) showed that a reduced photosynthetic capacity can be associated with a small rooting volume. Arp (1991) analyzed 14 observations and showed that a small rooting volume (pot size < 3-5 1) was probably responsible for photosynthetic acclimation under high CO^.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies, including some field studies, used plants grown in pots. Arp (1991) showed that rooting volume altered the response of plants to elevated [CO 2 ], and further experiments have reported a strong feedback when roots encounter a physical barrier (Masle et al 1990;Thomas & Strain 1991).…”
Section: Why Might Chamber Studies Be Insufficient?mentioning
confidence: 99%
“…Furthermore, soil temperature can affect photosynthesis, and as soil temperatures and photosynthesis increase together, changes in whole-plant source-sink relationships can occur (Lippu & Puttonen, 1991 ;Landhausser et al, 1996). For example, low soil temperatures can limit rates of enzymically driven root processes such as growth, nutrient uptake, and respiration, decreasing the demand for C and resulting in a negative feedback to photosynthesis through the accumulation of nonstructural carbohydrates in leaves (Thomas & Strain, 1991).…”
Section: mentioning
confidence: 99%